A Systematic Problem Validation Framework for Startups and Entrepreneurs - Velankar, Makarand; Thombre, Sneha; Wadkar, Harshad (AMC Indian Journal of Entrepreneurship, 2022)
Problem identification is typically the first crucial step in a startup. The problem should be worth solving and have market potential for sustainable and scalable business. Typically, the students who plan a startup struggle to find the right problem to work on. This paper proposes the systematic approach to form a well balanced team using self-discovery and identifying personality traits with passion. The closer the problem for the founder, greater the chance of success. Framework for problem identification and validation includes steps such as identification, design thinking, Jobs to be done (JTBD) framework, brainstorming, and back of the envelope calculation. Customer feedback and competition analysis are necessary to pinpoint the exact pain points and design the solution around these with a strong differentiator. The case studies provide further insights for better understanding of the concepts applied for the proposed startup venture. This paper will be useful for budding entrepreneurs to test their ideas at the initial stage or refine their solutions for the product-market fit to start a journey in the startup world.